Left ventricular chamber dilatation in hypertrophic cardiomyopathy: related variables and prognosis in patients with medical and surgical therapy. Issue 5 (November 1995) - Seiler, C.; Jenni, R.; Vassalli, G.; Turina, M.; Hess, O. M.
Abstract : BACKGROUND–To determine the incidence and prognosis of left ventricular dilatation and systolic dysfunction in 139 patients with hypertrophic cardiomyopathy during long term follow up. METHODS–Left ventricular chamber dilatation and systolic dysfunction (both together referred to as left ventricular chamber dilatation) were determined echocardiographically. Chamber dilatation was defined as an increase in the left ventricular end diastolic diameter of > 2% per year combined with a decrease in midventricular systolic fractional shortening of > 2% per year of follow up [10.3 (SD 6) years]. The predictive value for left ventricular chamber dilatation of clinical, invasive, and echocardiographic variables and its prognosis were assessed. RESULTS–In 119 of 139 individuals (86%), left ventricular chamber size and systolic function remained stable (group 1), and in 20/139 patients (14%) left ventricular chamber dilatation occurred during follow up (group 2). At baseline examination, symptoms such as dyspnoea and syncope occurred less often in group 1 than in group 2; New York Heart Association classification was lower in group 1 than in group 2 (P = 0.001). Left ventricular mass index relative to sex specific normal values was increased by 18% in group 1 and by 41% in group 2 (P = 0.04). Cumulative survival rates were slightly although not significantly higher in group 1 than in group 2. Event-free survival was significantly higher in group 1 than in group 2 (P < 0.05). CONCLUSIONS–(1) The development of left ventricular chamber dilatation and systolic dysfunction in hypertrophic cardiomyopathy occurs in approximately 1.5% of the patients per year. (2) Factors associated with left ventricular dilatation are dyspnoea, syncope, a higher functional classification, and a higher degree of left ventricular hypertrophy. (3) Patients with chamber dilatation have a worse prognosis than those without, particularly regarding quality of life.